Sound absorption by rubber coatings with periodic voids and hard inclusions. (1st January 2019) - Sharma, Gyani Shankar; Skvortsov, Alex; MacGillivray, Ian; Kessissoglou, Nicole
Abstract: Sound absorption by viscoelastic coatings for underwater applications comprising both periodically distributed voids and hard inclusions is presented. Using effective medium theory, each layer of gratings is approximated as a homogeneous medium with effective material and geometric properties, in which the monopole and dipole resonances of the inclusions are taken into account. A finite element model of the periodically distributed voided and hard inclusions in the host rubber medium is also developed. The different combinations of the layers are shown to have markedly different impacts on the acoustic performance, whereby the physical mechanisms governing sound absorption are strongly dependent on the Fabry-Pérot and dipole resonances associated with the presence of the inclusions. The effects of water backing or a steel backing plate are also shown to significantly affect the acoustic performance for the different layers of inclusions.